Pengaruh Kompetensi Dan Pengalaman Kerja Terhadap Kinerja Personel Polres Sampang Yang Dimediasi Oleh Disiplin Kerja - Hartono Hartono (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study is entitled the influence of competence and work experience on the performance of Sampang Police personnel mediated by work discipline. This type of research is explanatory research, the approach used is a quantitative approach, the research sample is 78 respondents. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) To describe competence, work experience, work discipline, and personnel performance at Polres Sampang. 2) To test and analyze whether there is a significant influence of competence on personnel performance at Polres Sampang. 3) To test and analyze whether there is a significant influence of work experience on personnel performance at Polres Sampang. 4) To test and analyze whether there is a significant influence of work discipline on personnel performance at Polres Sampang. 5) To test and analyze whether there is a significant influence of competence on work discipline at Polres Sampang. 6) To test and analyze whether there is a significant influence of work experience on work discipline at Polres Sampang. 7) To test and analyze whether there is a significant indirect influence of competence on personnel performance at the Polres Sampang with work discipline as an intervening variable. 8) To test and analyze whether there is a significant indirect influence of work experience on personnel performance at the Sampang Police with work discipline as an intervening variable. The research results show that: 1) competence has a positive insignificant effect on personnel performance. 2) work experience has a positive significant effect on personnel performance. 3) work discipline has a positive significant effect on personnel performance. 4) competence has a positive insignificant effect on work discipline. 5) work experience has a positive significant effect on work discipline. 6) competence on personnel performance through work discipline has a significant positive effect. 7) work experience on personnel performance through work discipline has a significant positive effect.